Development of a three-tier test to assess misconceptions about simple electric circuits - Peşman, Haki; Eryılmaz, Ali (My University, 2010)
The authors aimed to propose a valid and reliable diagnostic instrument by developing a three-tier test on simple electric circuits. Based on findings from the interviews, open-ended questions, and the related literature, the test was developed and administered to 124 high school students. In addition to some qualitative techniques for establishing the validity, some quantitative techniques were also used. Consequently, Cronbach's alpha reliability coefficient was estimated for the test as .69, and results revealed that the test scores could be a valid and reliable measure of students’ qualitative understanding of simple electric circuits.
Basit elektrik devreleri kavram yanılgılarını ölçmek amacıyla üç aşamalı bir test geliştirmek
Makale - Yabancı Dilde Makale
Keywords: Physics education; Misconceptions; Three-tier tests; Simple electric circuits